Anterior Cruciate Ligament Injuries in Children and Adolescents: A Review of the Recent Literature - Ziebarth, Kai; Kolp, D.; Kohl, Sandro; Slongo, Theddy (European Journal of Pediatric Surgery, 2013)
In contrast to the treatment of avulsion lesions of the anterior cruciate ligament (ACL) the management of intrasubstance ACL tears in the skeletally immature patient remains controversial. Prospective studies could show that conservative treatment results in severe instability with concomitant intraarticular damage and poor function of the knee. Reconstruction of a torn ACL always carries the risk of damaging the open growth plates; with consecutively affecting the longitudinal or axial growth of the lower extremity either on the femoral or the tibial side. Thus, several surgical procedures are available to prevent adverse events mentioned above. The purpose of this study is to review the recent literature regarding the treatment algorithm for ACL injuries in skeletally immature patients. This review will (1) investigate the indications for ACL surgery in children; (2) determine if a surgical procedure is clinically superior in skeletally immature patients; and (3) correlate the adverse events with the surgical technique.
Keywords: anterior cruciate ligament; surgery; children